Y RNAs are conserved endogenous RIG-I ligands across RNA virus infection and are targeted by HIV-1 - Vabret, Nicolas; Najburg, Valérie; Solovyov, Alexander; Gopal, Ramya; McClain, Christopher; Šulc, Petr; Balan, Sreekumar; Rahou, Yannis; Beauclair, Guillaume; Chazal, Maxime; Varet, Hugo; Legendre, Rachel; et al. (iScience, 2022)
Pattern recognition receptors (PRRs) protect against microbial invasion by detecting specific molecular patterns found in pathogens and initiating an immune response. Although microbial-derived PRR ligands have been extensively characterized, the contribution and relevance of endogenous ligands to PRR activation remains overlooked. Here, we characterize the landscape of endogenous ligands that engage RIG-I-like receptors (RLRs) upon infection by different RNA viruses. In each infection, several RNAs transcribed by RNA polymerase III (Pol3) specifically engaged RLRs, particularly the family of Y RNAs. Sensing of Y RNAs was dependent on their mimicking of viral secondary structure and their 5′-triphosphate extremity. Further, we found that HIV-1 triggered a VPR-dependent downregulation of RNA triphosphatase DUSP11 in vitro and in vivo, inducing a transcriptome-wide change of cellular RNA 5′-triphosphorylation that licenses Y RNA immunogenicity. Overall, our work uncovers the contribution of endogenous RNAs to antiviral immunity and demonstrates the importance of this pathway in HIV-1 infection. [Display omitted] •Y RNAs and other POL3 transcripts are RLRs ligands during RNA virus infections•Y RNA immunogenicity depends on their 5′-PPP and viral-mimicry secondary structure•Development of a novel sequencing approach to measure 5′-PPP status of RNA•HIV-1 VPR triggers DUSP11 downregulation and modulates host 5′-PPP transcriptome Biological sciences; Immunology; Transcriptomics